Association of non-high-density lipoprotein cholesterol-to-high-density lipoprotein cholesterol ratio (NHHR) with gout prevalence: a cross-sectional study - Guo, Xia; Chu, Haoxuan; Xu, Hanchi; Wang, Shipeng; He, Jiahuan; Wang, Yushi (Frontiers in Nutrition, 2024)
The non-high-density lipoprotein cholesterol (non-HDL-C)-to-highdensity lipoprotein cholesterol (HDL-C) ratio (NHHR) is a strong lipid marker that has been associated with atherogenic features. This study aimed to investigate the potential association between the NHHR and gout prevalence.: This study investigated the relationship between the NHHR and gout by analyzing data gathered from the National Health and Nutrition Examination Survey (NHANES), a research study conducted in the United States from 2007 to 2018. All participants in NHANES provided written informed consent prior to participation. The NHHR was calculated as the ratio of non-HDL-C to HDL-C. Total cholesterol (TC) and HDL-C levels were sourced from NHANES laboratory data. Gout was assessed using a questionnaire. Weighted logistic regression analysis, subgroup analysis, and smoothed curve fitting were performed.Results: This study included 30,482 participants. The fully adjusted models showed that for each unit increase in NHHR in continuous variables, there was a 10% higher likelihood of gout prevalence (OR: 1.10, 95% CI: 1.05, 1.16). Analysis of the NHHR quartiles revealed that patients in the highest quartile had a notably greater probability of developing gout than those in the lowest quartile. (Q4 vs. Q1, OR: 1.34, 95% CI:1.05, 1.71). Subgroup analyses yielded consistent results across categories, indicating a significant positive association between the NHHR and gout. E-value analysis suggested robustness to unmeasured confounding. Interaction tests showed that the race, education level, marital relationship, poverty-income ratio (PIR), hypertension, smoking habits, estimated glomerular filtration rate (eGFR), lipid-lowering therapy, and diabetes had no discernible effects on this association. The p-values for all the interactions were >0.05. Nevertheless, the relationship between the NHHR and gout was significantly affected by the age and sex of the participants (interaction p < 0.05).Among adults in the United States, elevated NHHR levels are correlated with increased odds of gout prevalence.